P107 Evolution of Imaging in the Preoperative Assessment of Patients Undergoing Ileal Pouch Surgery. (December 2019) - Wood, Trevor; Zaghiyan, Karen; Lightner, Amy; Fleshner, Phillip
Abstract : BACKGROUND: Ileal pouch-anal anastomosis (IPAA) is the standard operative approach for ulcerative colitis (UC) or inflammatory bowel disease unclassified (IBDu) patients with medical refractory disease or dysplasia. Pouchitis or denovo Crohn's disease are frequent adverse outcomes. The presence of small bowel (SB) mucosal inflammation before surgery might be an important predictor of these outcomes after surgery. Although small bowel follow through (SBFT) with barium has been the traditional imaging modality, cross sectional imaging using CT enterography (CTE) or MR enterography (MRE) have become increasingly utilized for preoperative SB assessment. The aim of this study was to assess changes in the utilization of SBFT versus CTE/MRE in UC and IBDu patients undergoing IPAA. METHODS: Prospectively generated clinical profiles on consecutive UC and IBDu patients undergoing IPAA between November 2006 and August 2019 were reviewed. Patients were classified into 2 groups: Group A (2006-2012) and Group B (2013-2019). Each patient was evaluated for preoperative SB imaging within their respective group. Baseline demographics were compared between groups. Imaging modalities included SBFT, CTE, MRE or 'no imaging'. RESULTS: The study cohort of 354 patients had a mean age of 37.3 years (SD 17.1) years and included 50% males. Group A included 196 (55%) patients and Group B included 158 (45%) patients. Groups were comparable in terms of age, gender, and indication for surgery. Patients in Group A had a significantly longer disease duration (115 vs 85 months, P = 0.01) and greater number of IBDU patients (37% vs 22%, P < 0.01) versus UC patients (64% vs 77%, P < 0.01). When comparing imaging modalities, there was a significantly higher use of SBFT in Group A (44% vs 4%, P < 0.01), significantly higher use of CTE and MRE in Group B (11% vs 27%, P < 0.01 and 7% vs 40%, P < 0.01, respectively), and no difference in 'no imaging' between the two groups (32% vs 29%, P = 0.56). CONCLUSION(S): Cross sectional imaging using CTE or MRE has become the preferred modality of preoperative SB imaging in UC and IBDu patients undergoing IPAA.